The SMUL_1544 Gene Product Governs Norcobamide Biosynthesis in the Tetrachloroethene-Respiring Bacterium Sulfurospirillum multivorans. - Keller, Sebastian; Treder, Aaron; Von Reuss, Stephan; Escalante-Semerena, Jorge C; Schubert, Torsten (My University, 2016)
The tetrachloroethene (PCE)-respiring bacterium Sulfurospirillum multivorans produces a unique cobamide, namely, norpseudo-B12, which, in comparison to other cobamides, e.g., cobalamin and pseudo-B12, lacks the methyl group in the linker moiety of the nucleotide loop. In this study, the protein SMUL_1544 was shown to be responsible for the formation of the unusual linker moiety, which is most probably derived from ethanolamine-phosphate (EA-P) as the precursor. The product of the SMUL_1544 gene successfully complemented a Salmonella enterica ΔcobD mutant. The cobD gene encodes an l-threonine-O-3-phosphate (l-Thr-P) decarboxylase responsible for the synthesis of (R)-1-aminopropan-2-ol O-2-phosphate (AP-P), required specifically for cobamide biosynthesis. When SMUL_1544 was produced in the heterologous host lacking CobD, norpseudo-B12 was formed, which pointed toward the formation of EA-P rather than AP-P. Guided cobamide biosynthesis experiments with minimal medium supplemented with l-Thr-P supported cobamide biosynthesis in S. enterica producing SMUL_1544 or S. multivorans Under these conditions, both microorganisms synthesized pseudo-B12 This observation indicated a flexibility in the SMUL_1544 substrate spectrum. From the formation of catalytically active PCE reductive dehalogenase (PceA) in S. multivorans cells producing pseudo-B12, a compatibility of the respiratory enzyme with the cofactor was deduced. This result might indicate a structural flexibility of PceA in cobamide binding. Feeding of l-[3-(13)C]serine to cultures of S. multivorans resulted in isotope labeling of the norpseudo-B12 linker moiety, which strongly supports the hypothesis of EA-P formation from l-serine-O-phosphate (l-Ser-P) in this organism. IMPORTANCE: The identification of the gene product SMUL_1544 as a putative l-Ser-P decarboxylase involved in norcobamide biosynthesis in S. multivorans adds a novel module to the assembly line of cobamides (complete corrinoids) in prokaryotes. Selected cobamide-containing enzymes (e.g., reductive dehalogenases) showed specificity for their cobamide cofactors. It has recently been proposed that the structure of the linker moiety of norpseudo-B12 and the mode of binding of the EA-P linker to the PceA enzyme reflect the high specificity of the enzyme for its cofactor. Data reported herein do not support this idea. In fact, norpseudo-B12 was functional in the cobamide-dependent methionine biosynthesis of S. enterica, raising questions about the role of norcobamides in nature.